Antibiotic residues and heavy metals in pork at wet markets in Vietnam - Tran Thi Tuyet Hanh; Sinh Dang Xuan; Hung Nguyen-Viet; Unger, Fred; Chu Van Tuat; Ngan Tran Thi; Phuc Pham Duc (Hanoi School of Public Health, 2015)
From April 2014 to January 2015, a total of 190 fresh pork samples at wet markets were collected to produce 18 pooled samples that represent 18 studied communes in Hung Yen and Nghe An provinces. Tetracycline, fluoroquinolones, sulfonamide, chloramphenicol groups were firstly screened by ELISA and positive samples were quantified by liquid chromatography–mass spectrometry/mass spectrometry (LCMS/MS). Lead, cadmium and arsenic were determined by Atomic Absorption Spectrometer (AAS). While pooled samples for tetracycline and fluoroquinolones (0/18) were negative tested we found positive test results for sulfonamide (50%, 9/18) and chloramphenicol (16.7%, 3/18). The average residue levels were 155.5 (25.6-263.2) µg/kg for sulfadimidine, higher than Vietnamese MRL (100 µg/kg) and 0.54 (0.34- 0.76) µg/kg for chloramphenicol, which is prohibited in veterinary drugs in Vietnam. Regarding heavy metals, there were 5/18 (27.8) of pooled samples being positive for lead, while cadmium and arsenic were not detected. The average concentration of lead in pork was 74.1 (70.1-78.7) µg/kg, which was still lower than the standard level applied for lead in pork (100 µg/kg). There were no significance differences on the prevalence and concentrations of antibiotic and heavy metal residues between the two studied provinces. The results highlight the presence of sulfadimidine and chloramphenicol in pork available at wet markets. This finding is a component of an ongoing food safety project (PigRISK), which is assessing the health risks of chemical hazards in pork and developing incentive-based innovations to improve management of human and animal health risks in smallholder pig value chains in Vietnam.